2022
DOI: 10.1101/2022.01.18.22269330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Effectiveness of COVID-19 Vaccines in preventing Infectiousness, Hospitalization and Mortality: A Historical Cohort Study Using Iranian Registration Data During Vaccination program”

Abstract: Background: There are some concerns about the effectiveness of the inactivated and vector-based vaccines against SARS-CoV-2 in the real-world settings with the emergence of new mutations, especially variants of concern. Data derived from administrative repositories during mass-vaccination campaigns or programs are of interest to study vaccine effectiveness (VE). Methods: Using 4-repository administrative data linkage, we conducted a historical cohort study on a target population of 3,628,857 inhabitants aged… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…This shows the effect of the vaccine on preventing hospitalization, which is consistent with the results of other studies. Mirahmadizadeh et al conducted a study comparing the effectiveness of vaccines in Iran, their results showed that the implementation of the vaccination plan, including all available vaccine options in Iran, led to a significant reduction in the incidence of COVID-19, and hospitalization related to COVID-19 was remarkedly decreased (26).…”
Section: Discussionmentioning
confidence: 99%
“…This shows the effect of the vaccine on preventing hospitalization, which is consistent with the results of other studies. Mirahmadizadeh et al conducted a study comparing the effectiveness of vaccines in Iran, their results showed that the implementation of the vaccination plan, including all available vaccine options in Iran, led to a significant reduction in the incidence of COVID-19, and hospitalization related to COVID-19 was remarkedly decreased (26).…”
Section: Discussionmentioning
confidence: 99%
“…In phase III clinical trial, which is currently under peer-review, a two-dose vaccine regimen was well tolerated, with no safety concerns, and conferred 70.5% and 83.1% efficacy against hospitalization and ICU admission, respectively. The vaccine has reduced hospitalization by 86.4% and deaths by 98.3% (12).…”
mentioning
confidence: 99%